2010
DOI: 10.1016/j.jconrel.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

γ-Polyglutamic acid-coated vectors for effective and safe gene therapy

Abstract: In the present study, we developed some novel gene delivery vectors, coated cationic complexes with γ-polyglutamic acid (γ-PGA) for effective and safe gene therapy. Cationic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 33 publications
0
55
0
1
Order By: Relevance
“…Also, we found that γ-PGA complex was taken up by γ-PGA-specific receptormediated endocytotic pathway. 8,11) We discovered that the γ-PGA-coated complex showed high gene expression selectively in the marginal zone of the spleen (Figs. 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that γ-PGA complex was taken up by γ-PGA-specific receptormediated endocytotic pathway. 8,11) We discovered that the γ-PGA-coated complex showed high gene expression selectively in the marginal zone of the spleen (Figs. 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…1 Non-viral lipid carriers have been developed within recent years as an alternative to viral type gene vectors. They are mostly cationic lipid-based gene delivery systems which were developed as tools for gene delivery e.g., 2,3 (for a review see ref. 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various physicochemical and biological differences based on their different side chains have been reported to affect their affinity for nucleic acids and the resultant polyplex structures [4,5]. The transfection efficiency of PR is higher than that of PK [6,7], and whether this disparity is due to the difference in their affinities or polyplex structures remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%